The Effect of Methanol Concentration on the Extraction of Moringa Leaf (Moringa oleifera) and Papaya Fruit (Carica papaya) on Elastase and Hyaluronidase Installing Activities - Sugihartini, Nining; Nur, Mohamad Usman; Yuliani, Sapto (Open Access Macedonian Journal of Medical Sciences, 2022)
Abstract BACKGROUND OF THE STUDY: Β-carotene, flavonoids and phenolic compounds found in methanol extracts of Moringa leaves and papaya fruit have high antioxidant activity so that they can be used for antiaging. The concentration of solvent is a factor that will affect the levels of active ingredients in methanol extract. This study aims to determine the effect of the concentration of the methanol solvent derived from the extraction of Moringa leaves and papaya fruit on the inhibitory activity of the elastase and hyaluronidase enzymes. AIM OF THE STUDY: Knowing the best extracts of methanol 50, 70, and 96% of Moringa leaf (Moringa oleifera) and papaya fruit (Carica papaya) as antiaging agents through inhibition of elastase and hyaluronidase enzymes. METHODOLOGY: In this study variations in the concentration of methanol 50%, 70%, and 96% were used for the extraction of Moringa leaves and papaya fruit. The extract was obtained by maceration method which was then tested for the inhibition of the enzyme activity of elastase and hyaluronidase using ELISA (Enzyme-Linked Immunosorbent Assay). RESULTS: The results of the elastase enzyme inhibitory activity test on Moringa leaf extract with 50%, 70%, and 96% methanol solvents IC50 respectively = 9453.38; 6604.70; 12346.44 μg / mL, while the yield of papaya extract 5995.31; 9046.25; 11571.54 μg / mL. In addition, the test results showed the inhibitory activity of the hyaluronidase enzyme showed that the Moringa leaf extract with 50%, 70%, and 96% solvents IC50 respectively = 2944.53; 1028,36; 3001.83 μg / mL, while the yield of methanol extract of papaya fruit is 982.67; 2982.96; 3530.18 μg / mL. CONCLUSION: Based on the test results it can be concluded that the most effective solvent concentration as an inhibition of the enzyme elastase and hyaluronidase methanolic extract of Moringa leaves is 70% methanol solvent. While papaya fruit methanol extract which is effective in inhibiting the enzymes elastase and hyaluronidase is 50% methanol solvent.